The isometric muscle contraction tasks or repetitive movements to evaluate the effects of fatigue. A systematic review - Peinado Palomino, D.; Torres Pareja, M.; Mordillo Mateos, L.; Mendoza Láiz, N. (Archivos de medicina del deporte, 2018)
Fatigue has been defined as a phenomenon related to the time of decrease of the maximum capacity of generation of force, expressing itself, generally, as a deterioration in the maximum voluntary contraction (CMV). The appearance of fatigue in skeletal muscle during an effort has long been of interest to physiologists, especially because fatigue is a limiting factor in athletic performance or in the performance of any task. The aim of the article is to analyze the literature and provide a systematic review on fatigue induced by muscle contraction tasks, caused by isometric contractions or by finger tapping. To this end, an investigation was carried out based on the PRISMA methodology (Articles of preferred reports for systematic reviews and meta-analyzes). Conducting a search of articles in the PubMed, Medline, Science Direct and Google Scholar databases, between the months of June and November of 2017 after the year 2000. Of the 315 studies initially identified, only 12 complied with the established selection criteria. The methodological variability of the different studies allows to observe how through the tapping tasks (repetitive movements of fingers), or through isometric contraction tasks, it is possible to determine the different parameters of fatigue that are evaluated in each study, being a very used to address that topic. Muscle fatigue has been predominantly studied when induced by isometric tasks, with a greater number of investigations using this type of methodology, since, although finger tapping is a reliable procedure to evaluate the underlying neurophysiological mechanisms of fatigue, It has been explored.